Effects of immunological and hematological parameter in mice exposed to mixture of volatile organic compounds. (20th March 2016) - Wang, Fan; Liu, Fei; Liu, Haifang; Chen, Wanguang; Si, Xianli; Ma, Xiuying
Abstract: Exposure to some kinds of volatile organic compounds (VOCs) leads to immune system disorders, liver and kidney damage, hematological change. However, there is little information about the effect of VOCs mixture on immune system and hematological parameter. In this study, 50 Kunming male mice were exposed in five similar chambers, 0 (control) and four different doses of VOCs mixture (G1–4) for consecutively 10 days at 2 h/day. The concentrations of VOCs mixture were as follows: formaldehyde, benzene, toluene and xylene 1.0 + 1.1 + 2.0 + 2.0, 3.0 + 3.3 + 6.0 + 6.0, 5.0 + 5.5 + 10.0 + 10.0 and 10.0 + 11.0 + 20.0 + 20.0 mg/m 3, respectively, which corresponded to 10, 30, 50 and 100 times of indoor air quality standard in china. One day following VOCs exposure, spleen T lymphocyte subpopulation, serum biochemical markers and peripheral blood cells in mice were analyzed, respectively. VOCs exposure decreased significantly erythrocyte count (RBC), platelet (PLT) in peripheral blood in mice. While aspartate aminotransaminase (AST), alanine aminotransaminase (ALT), alkaline phosphatase (ALP) and creatinine (CREA) in serum increased significantly in G4 mice versus controls. Flow cytometry analysis showed that the number of splenic lymphocyte subpopulation cells decreased significantly in G2, 3 and 4 mice in comparison with normal Kunming mice. These results indicate inhalation of VOCs mixture affects CD4/8 subpopulations, liver, kidney function and some hematological parameters in mice.